The Changed Route of Anterior Tibial Artery due to Healed Fracture - Kemal Gökkuş; Ergin Sagtas; Nuri Comert; Mehmet Bekir Unal; Murat Baloglu (Case Reports in Vascular Medicine)
We would like to highlight unusual sequelae of healed distal third diaphyseal tibia fracture that was treated conservatively 36 years ago, in which we incidentally detected peripheral CT angiography. The anterior tibial artery was enveloped three-quarterly by the healing callus of the bone (distal tibia).